Laonice Malmgren, 1867 (Annelida: Spionidae) from the Aysén region in southern Chile with description of a new species - Delgado-Blas Víctor Hugo; Díaz-Díaz, Oscar; Rozbaczylo, Nicolás (Zootaxa, 2024)
Specimens of Laonice collected from southern Chile were examined, and one new species was described. Laonice ayseniensis sp. nov. is characterized by having an anteriorly fused prostomium and peristomium, giving a bicornate, cap-shaped appearance; nuchal organs and caruncle extending up to chaetigers 14–16; very small, subtriangular first notopodial postchaetal lamellae, shorter than the neuropodial lamellae; leaf-like notopodial postchaetal lamellae in the branchial region, with pairs 4, 13, and 14 larger and wider than the other pairs; very low dorsal transverse ridges on chaetigers 37–48; the first neuropodial postchaetal lamellae rectangular with rounded edges, oval with earlobe-shaped ventral edges on chaetigers 2–8; ventrolateral pouches from chaetigers 35–48 up to chaetiger 57; hooded hooks with a distal opening; a pygidium with two small ventral papilliform cirri arranged close to each other and five long cirri. Additional information about the morphological characters of L. praecirrata Hartmann-Schröder, 1965 is provided, using material collected near to the type locality. An identification key for all South American species is provided.